Peningkatan Kesiapan UKM untuk Mengikuti Export Coaching Program - Abdillah Sani (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2019)
This study discusses the change project in the form of coaching activities carried out in order to further increase the readiness of potential SMEs to become prospective participants of the Export Coaching Program at the Indonesia Export Training Center (IETC) - Ministry of Trade. The model used is the First Phase (stage I) of the 3 Phase Export Coaching Program activities carried out since 2010 by PPEI colaborate with the Trade Fascilitation Office, Canada. In this first stage, the participants went through is the Identification of the Company's Internal Potential and the Market Potential of the Export Destination Country. From the identification of the company's internal potential, it will be known the strengths and weaknesses of the company to be able to export, while from the identification of market potential will be known opportunities and challenges in realizing export plans. Identification of these two factors, followed by a SWOT analysis, preparation of an action plan and a Business Plan. The method used is coaching as well as research applied through a series of consultancy activities, observation, direct guidance and distance guidance. Research subjects were 7 company owners located in the city of Depok, West Java. Data collection is done by recording observations, interviews, consultancy and giving direction. The analysis uses descriptive analysis techniques. Based on the results of the analysis it is known that among others: a) the level of attendance and participation of the participants reached an average of 91.75% b) the level of satisfaction of participants in participating in this activity: 5 people (71.43%) expressed satisfaction and 2 people (28.57%) expressed very satisfied; c) about the readiness to take part in the export coaching program at PPEI: 4 people (57.13%) said they were ready, 3 people (42.47%) said they were neutral, d) on the question of whether they were ready if currently getting buyers: 3 people ( 42.86%) said they were ready, 3 people (42.86%) said they were not ready and 1 person (14.29%) said they were neutral.